Sosialisasi Penerapan Pembelajaran Berbasis Diferensiasi pada Perangkat Pembelajaran Sekolah Se-Kecamatan Pringgasela - Zaidah, Alpi; Prayunisa, Fena; Irwansah, Irwansah; Mahariyanti, Ermila; Usman, Usman; Hidayanti, Hidayanti; Sait, Sahrul (Lembaga Publikasi Ilmiah Nusantara, 2025)
The Merdeka Curriculum emphasizes the importance of student-centered learning, with differentiated instruction as one of its core pedagogical approaches. However, many teachers still face challenges in translating this concept into contextual and adaptive lesson planning. This program aimed to improve teachers’ conceptual understanding and practical skills in designing differentiated instructional materials responsive to student diversity. The activity was conducted at SMPN 1 Pringgasela, East Lombok Regency, involving 35 elementary and junior high school teachers from various schools in the Pringgasela sub-district. The methods included material dissemination, case analysis, independent practice, as well as reflection and evaluation sessions. The results showed a significant improvement in participants’ understanding of differentiated instruction principles and the emergence of initial competence in developing adaptive lesson plans. These findings suggest that participatory and practice-based training approaches are effective in enhancing teacher capacity. Further training and technical mentoring are recommended to support the sustainable implementation of the Merdeka Curriculum at the school level.